2006
DOI: 10.3748/wjg.v12.i27.4369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin-sensitizing agents in combination with ezetimibe, and valsartan in rats with non-alcoholic fatty liver disease

Abstract: Combination therapies have a greater effect on liver fat content as compared to monotherapy. Rosiglitazone appears to improve hepatic steatosis to a greater extent than metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 50 publications
7
35
0
Order By: Relevance
“…These findings sug gest that insulin resistance contributes to the development of NAFLD and that insulin sensitizers may represent important agents for the treatment of NAFLD. Furthermore, the beneficial effects of insulin-sensitizing agents, RGZ [21,22] , pioglitazone [12] and [21] , on hepatic steatosis and inflammation have been confirmed in various animal models of NAFLD. Compared to metformin, RGZ appears to be a better drug for improving hepatic steatosis [21] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These findings sug gest that insulin resistance contributes to the development of NAFLD and that insulin sensitizers may represent important agents for the treatment of NAFLD. Furthermore, the beneficial effects of insulin-sensitizing agents, RGZ [21,22] , pioglitazone [12] and [21] , on hepatic steatosis and inflammation have been confirmed in various animal models of NAFLD. Compared to metformin, RGZ appears to be a better drug for improving hepatic steatosis [21] .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the beneficial effects of insulin-sensitizing agents, RGZ [21,22] , pioglitazone [12] and [21] , on hepatic steatosis and inflammation have been confirmed in various animal models of NAFLD. Compared to metformin, RGZ appears to be a better drug for improving hepatic steatosis [21] . In line with the above reports [12,21,22] , our study showed that increased liver weight and liver weight index, elevated serum liver enzyme levels and altered liver histological conditions including steatosis, inflammation and fibrosis were observed in the NAFLD rats, which were significantly improved 4 wk after RGZ treatment.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, ezetimibe has been reported to reduce postprandial hypertriglyceridaemia and inflammation and to improve insulin sensitivity 15,16) . In animals experiments, ezetimibe reversed dietinduced obesity 17,18) , liver steatosis [17][18][19][20] , and insulin resistance 19) . In humans, in addition to the effect of ezetimibe on lowering serum LDL-C 13) , its potential effects on liver steatosis 21) and insulin resistance 22) have been reported.…”
Section: Measurement Of Serum Samplesmentioning
confidence: 95%
“…For example, compared with weight loss alone, the administration of ezetimibe plus weight loss in 25 obese subjects significantly decreased intrahepatic triglyceride content (-18%), as well as plasma hsCRP (-53%), interleukin-6 (-24%), LDL-C (-18%), and campesterol (-59%) concentration (all P < 0.05) [17] . Furthermore, combined treatment of ezetimibe with insulin-sensitizing agents had greater effect on hepatic fat content and lipid peroxidation compared to monotherapy in the methionine choline-deficient diet rat model of NAFLD [18] . Interestingly, the combination of ezetimibe and acarbose for 24 wk reduced steatosis, inflammation and fibrosis in the liver, compared with long-term monotherapy with either drug, in a high-fat diet-induced NAFLD mouse model (C57BL/6J mice) [19] .…”
Section: Role Of Drug Combinations Including Ezetimibe In Nafldmentioning
confidence: 93%